What Drives Innovation and How Its Relevance is Established. A Perspective on Electric Vehicle Promotion in La Rochelle and Gothenburg : 1989-2000 - Marika Rupeka (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
For the past few years, in France and in Sweden, electric vehicle promotion has been pursued as part of a political strategy to decrease greenhouse gas emissions within the transport sector, thus tackling climate change. From a general perspective, transport electrification is presented as a relevant technological choice given the structure of electric energy production processes that are nuclear-based in France and correspond to a mix of renewable sources in Sweden. It is believed that the complexity of environmental impacts can be assessed fully through technology life cycle analysis. Beyond the climate and environmental health discourse there is also a strong motivation to conquer new markets by means of “green” technologies. What binds these motives and how do they affect urban territories? To shed light upon this inquiry, this research paper offers a parallel case study on electric vehicle promotion strategies in Gothenburg and La Rochelle urban agglomerations in the 1990s. By asking why territories innovate and how they determine the relevance of specific organisational and technological solutions, the aim is to contribute to an historic scholarly debate on the need to study motives that drive territorial innovation as much as the transformation process itself. This research paper reveals that there are (at least) three different perspectives from which the relevance of technological solutions for specific territorial contexts is established: 1/ the local political history perspective, 2/ the international perspective, 3/ the individual (user) perspective. On all three levels by means of motivations, attitudes, vocabularies, and methods corporate cultures and agendas translate into the narratives arguing the relevance of territorial innovation.